Bile acid synthesis in the Smith-Lemli-Opitz syndrome: effects of dehydrocholesterols on cholesterol 7α-hydroxylase and 27-hydroxylase activities in rat liver - Akira Honda (Journal of Lipid Research, 1999)
The Smith-Lemli-Opitz syndrome (SLOS) is a congenital birth defect syndrome caused by a deficiency of 3β-hydroxysterol Δ7-reductase, the final enzyme in the cholesterol biosynthetic pathway. The patients have reduced plasma and tissue cholesterol concentrations with the accumulation of 7-dehydrocholesterol and 8-dehydrocholesterol. Bile acid synthesis is reduced and unnatural cholenoic and cholestenoic acids have been identified in some SLOS patients. To explore the mechanism of the abnormal bile acid production, the activities of key enzymes in classic and alternative bile acid biosynthetic pathways (microsomal cholesterol 7α-hydroxylase and mitochondrial sterol 27-hydroxylase) were measured in liver biopsy specimens from two mildly affected SLOS patients. The effects of 7- and 8-dehydrocholesterols on these two enzyme activities were studied by using liver from SLOS model rats that were treated with the Δ7-reductase inhibitor (BM15.766) for 4 months and were comparable with more severe SLOS phenotype in plasma and hepatic sterol compositions. In the SLOS patients, cholesterol 7α-hydroxylase and sterol 27-hydroxylase were not defective. In BM15.766-treated rats, both enzyme activities were lower than those in control rats and they were competitively inhibited by 7- and 8-dehydrocholesterols. Rat microsomal cholesterol 7α-hydroxylase did not transform 7-dehydrocholesterol or 8-dehydrocholesterol into 7α-hydroxylated sterols. In contrast, rat mitochondrial sterol 27-hydroxylase catalyzed 27-hydroxylation of 7- and 8-dehydrocholesterols, which were partially converted to 3β-hydroxycholestadienoic acids. Addition of microsomes to the mitochondrial 27-hydroxylase assay mixture reduced 27-hydroxydehydrocholesterol concentrations, which suggested that 27-hydroxydehydrocholesterols were further metabolized by microsomal enzymes. These results suggest that reduced normal bile acid production is characteristic of severe SLOS phenotype and is caused not only by depletion of hepatic cholesterol but also by competitive inhibition of cholesterol 7α-hydroxylase and sterol 27-hydroxylase activities by accumulated 7- and 8-dehydrocholesterols. Unnatural bile acids are synthesized mainly by the alternative pathway via mitochondrial sterol 27-hydroxylase in SLOS.— Honda, A., G. Salen, S. Shefer, A. K. Batta, M. Honda, G. Xu, G. S. Tint, Y. Matsuzaki, J. Shoda, and N. Tanaka. Bile acid synthesis in the Smith-Lemli-Opitz syndrome: effects of dehydrocholesterols on cholesterol 7α-hydroxylase and 27-hydroxylase activities in rat liver. J. Lipid Res. 1999. 40: 1520–1528.